Linguistic Profile Test (LPT) in Nepali Language - Karna, Sureshwar Lal; Karantha, Pratibha; Khanal, Kabiraj (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10153 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 8-9 = 5 <=5> 1 =5 *" 05 7. 7 "( # . !# ## /& # H)&&2)&&+ G J "( # 7 # # . F0 ! )B?%&)A2&&#)BBAB 7*B) 9 0 ! =5 #